Ecological Impacts of Eucalypts - Myths and Realities - Abbasi, S. A.; Vinithan, S. (Indian Forester, 1997)
Eucalypts haVe become the focal point of a raging controversy over the past two decades vis-a-vis their impacts on the environment. No genera of trees has attracted such intense and acrim.onious debate on its perceived ills and virtues as Eucalypts. The views for or against Eucalypts have become so polarized that at times the eriticism or appreciation is based solely on prejudice than ona balanced consideration of the facts. In this paper we have examined the views for and against Eucalypts in the background of the evidence reported by the various authors to back their views.